ENHANCE THE EFFICIENCY OF RMIL’S FORMULA FOR MINIMUM PROBLEM - MUSTAFA , AHMED ANWER (Journal of Duhok University, 2021)
In this paper, a new formula of is suggested for conjugate gradient method of solving unconstrained optimization problems based on depends on the creation and update of RMIL’S formula with the inclusion of a parameter and step size of cubic. Our novel proposed CG-method has descent condition and global convergence properties. Numerical comparisons with standard conjugate gradient algorithm of RMIL’S formula show that this algorithm very effective depending on the number of iterations and the number of functions evaluation.